2015
DOI: 10.1021/acs.chemmater.5b01813
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous In–Ga–Zn Oxide Semiconducting Thin Films with High Mobility from Electrochemically Generated Aqueous Nanocluster Inks

Abstract: Solution processing is a scalable means of depositing large-area electronics for applications in displays, sensors, smart windows, and photovoltaics. However, solution routes typically yield films with electronic quality inferior to traditional vacuum deposition, as the solution precursors contain excess organic ligands, counterions, and/or solvent that leads to porosity in the final film. We show that electrolysis of aq. mixed metal nitrate salt solutions drives the formation of indium gallium zinc oxide (IGZ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 67 publications
1
48
0
Order By: Relevance
“…This method, recently coined "Prompt Inorganic Condensation", or PIC, has been used to make high quality films of a number of oxides, including dielectrics, [53][54][55][56][57][58] transparent conducting oxides, 59,60 and high-resolution inorganic resists. 61,62 In these examples using PIC, dehydration and nitrate removal are shown to occur without negatively affecting film morphology, allowing the preparation of dense, smooth films at relatively low temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…This method, recently coined "Prompt Inorganic Condensation", or PIC, has been used to make high quality films of a number of oxides, including dielectrics, [53][54][55][56][57][58] transparent conducting oxides, 59,60 and high-resolution inorganic resists. 61,62 In these examples using PIC, dehydration and nitrate removal are shown to occur without negatively affecting film morphology, allowing the preparation of dense, smooth films at relatively low temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly,g allium oxide exhibits aw eakc rystalline phase with broad reflexes which corresponds to the "d-Ga 2 O 3 "p hase. [26] The homogeneity of the coated films from the urea nitrate precursors on aS i/SiO 2 substrate as well as their microstructure was investigated via high-resolution transmission electron mi- (Figure 7a,b) revealed that films annealed at both temperatures are amorphous in nature with the absence of anyp artial film crystallinity amorphous matrix. It is known that gallium oxide displays ab road phase distribution depending on the type of precursor used and the thermalc alcination history under which this material is obtained.T his allows to form different crystalline phases or even mixtures therefrom.…”
Section: Resultsmentioning
confidence: 99%
“…In recent two decades, solution‐processed semiconductors and their devices have attracted increasing attentions, because the solution method allows deposition of thin films in air via a roll‐to‐roll process and/or by the directly patterning printing without incorporating photolithography for mass production, and possesses some other beneficial features such as the precise control of the cation‐anion stoichiometry together with metal cation ratios . To date, a variety of solution‐processable metal oxide semiconductors such as indium zinc oxide (In‐Zn‐O), zinc tin oxide (Zn‐Sn‐O), indium gallium zinc oxide (In‐Ga‐Zn‐O), and zinc indium tin oxide (Zn‐In‐Sn‐O), have been extensively explored as potential channel materials for thin‐film transistor (TFT) application providing reasonable electrical characteristics. Among all of these oxide semiconductors, amorphous/nanocrystalline In‐Ga‐Zn‐O is investigated most frequently, because it demonstrates outstanding electrical performance and meter‐scale uniformity in vacuum‐based processing, and has been commercially used as the channel material of TFTs for backbone electronics of active matrix liquid crystal displays (AMLCDs) and active‐matrix organic light‐emitting diode displays (AMOLEDs) .…”
Section: The Comparison In Performance Of In‐ga‐zn‐o and In‐ga‐cd‐o Tmentioning
confidence: 99%
“…This indicates that a small change is reflected in the thermal‐driven condensation processes substituting Zn with Cd. In this work, the final annealing temperature for InGaCd x O samples is fixed at a frequently used 400 °C in the solution‐processed In‐Ga‐Zn‐O films …”
Section: The Comparison In Performance Of In‐ga‐zn‐o and In‐ga‐cd‐o Tmentioning
confidence: 99%